The Strategy Project: An Exploration of Enhancing Self-Regulated Learning in an Introductory Psychology Course - Valerie Whittlesey; Hillary H. Steiner (Park University, 2021)
College success requires development of self-regulated learning skills. This study describes a self-regulated learning strategy intervention in a large general education Introductory Psychology course, focusing on the second exam. Students' reflection responses across five time periods were compared with exam performance. Increased self-regulated learning strategies usage correlated with decreased passive learning strategies usage, increased hours of study, and increased academic performance. Strategy project interventions can be effective for introductory courses. However, because students may revert to passive strategies that worked in the past, strategy instruction should be extended throughout a course.